The Importance of Work Satisfaction in Mediating The Relationship Between Superleader and Employee Performance - Fristin, Yuntawati (JPAS (Journal of Public Administration Studies), 2018)
This research aims to analyse and explain the effect of Superleader on Work Satisfaction; the effect of Superleader on work performance; and the effect of Work Satisfaction on Work Performance. The number of samples used in this research is 240 people. The data is analysed by using Generalized Structured Component Analysis (GSCA). The result shows that Superleader has both positive and signifficant effect on work satisfaction, Superleader has positive effect but insignificant on work performance, and Job satisfaction has a positive and signifficant effect as well on work performance. While the indirect relationship between Superleader and Performance mediated by Job Satisfaction based on Sobel test shows significant effect.Â